Sources and distribution of polycyclic aromatic hydrocarbons (PAHs) and organic matter in surface sediments of an estuary under petroleum activity influence, Todos os Santos Bay, Brazil. Issue 2 (30th June 2017) - Nascimento, Rodrigo A.; de Almeida, Marcos; Escobar, Narayana C.F.; Ferreira, Sergio L.C.; Mortatti, Jefferson; Queiroz, Antônio F.S.
Abstract: The present study evaluated the origin and distribution of polycyclic aromatic hydrocarbons (PAHs) and the organic matter (OM) in the surface sediment of the São Paulo River estuary, Todos os Santos Bay (TSB), Brazil. The samples were collected in the rainy (CP1) and the dry (CP2) seasons. We analyzed the 16 PAHs from the United States Environmental Protection Agency (US EPA) priority pollutant list, total organic carbon (TOC), total nitrogen (N), and stable carbon isotope (δ 13 C). The total concentration of PAHs ranged from 11.45 ± 1.28 to 1825.35 ± 107.96 ng g − 1, while TOC ranged from 3.8 to 27.7 g kg − 1 . CP1 showed the highest concentrations for all parameters. The δ 13 C ratio indicated terrigenous OM (− 23.81 to − 26.63‰). The TOC/N ratio (C/N) indicated transitional OM (12.32 to 24.39), in addition to the continental origin. The diagnostic ratios of PAHs origin revealed only pyrolytic source, although close to areas with a history of petroleum contamination. Highlights: The highest TOC and PAHs concentrations occurred in season of higher pluviosity. High molecular weight PAHs predominated in all samples. C3 plants were the main organic matter source in the estuary. Diagnostic ratios of PAHs indicated pyrolytic source in rainy and dry season. The São Paulo River estuary presented from moderate to low contamination level